2017
DOI: 10.1038/boneres.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the vitamin D requirements during pregnancy

Abstract: Pregnancy represents a dynamic period with physical and physiological changes in both the mother and her developing fetus. The dramatic 2–3 fold increase in the active hormone 1,25(OH)2D concentrations during the early weeks of pregnancy despite minimal increased calcium demands during that time of gestation and which are sustained throughout pregnancy in both the mother and fetus suggests an immunomodulatory role in preventing fetal rejection by the mother. While there have been numerous observational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 129 publications
2
100
1
9
Order By: Relevance
“…The population-specific differentiation associated with the variant rs222016 is consistent with the differential evolution of the vitamin D system between populations—likely in response to different environments and associated changes in skin pigmentation 70,71 . Our results provide evolutionary context for the link between vitamin D and pregnancy outcomes 72 and suggest a role for variation in the gene GC in the ethnic disparities in pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 67%
“…The population-specific differentiation associated with the variant rs222016 is consistent with the differential evolution of the vitamin D system between populations—likely in response to different environments and associated changes in skin pigmentation 70,71 . Our results provide evolutionary context for the link between vitamin D and pregnancy outcomes 72 and suggest a role for variation in the gene GC in the ethnic disparities in pregnancy outcomes.…”
Section: Resultsmentioning
confidence: 67%
“…Consistent with our findings, an open‐label randomized controlled trial showed that maternal vitamin D supplementation (2,000–4,000‐IU cholecalciferol) among women with VDD/insufficiency from 12 to 16 weeks of gestation until delivery prevents neonatal VDD (Rodda et al, ). It is likely that placental transportal sites, notably megalin–cubilin system, are saturated with taking a certain dose of vitamin D a day (Hollis & Wagner, ). Though vitamin D is not considered a teratogen, this may be a protective mechanism to regulate foetal vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems crucial to initiating vitamin D supplementation earlier and eliminating VDD before pregnancy (Hollis & Wagner, 2017b). Moreover, it has been suggested that achieving serum 25(OH)D concentration of at least 100 nmol L −1 is required for optimizing the conversion of 25(OH)D to 1,25(OH)2D and reducing the adverse pregnancy outcomes (Hollis & Wagner, 2017a).…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Foetal hypercelcemia is an old concept that is confusing [26]; some reported hypercalcemias could have been not due to vitamin D excess leading to supravalvular aor-DOI: 10.1159/000487370 tic stenosis but due to a disease known as William' Syndrome in which patients exhibit an exaggerated response of circulating 25(OH)D to orally administrated vitamin D [27][28][29][30]. However, in the 1950s, the policy to fortify milk and cereals with Vitamin D in the United Kingdom increased the number of cases of Infantil Hypercalcemia that was half reduced when the fortification was limited [31].…”
Section: Vitamin D Intake Recommendations During Pregnancymentioning
confidence: 99%